Routine labour epidural analgesia versus labour analgesia on request: a randomised non‐inferiority trial1. (22nd May 2014) - Wassen, MMLH; Smits, LJM; Scheepers, HCJ; Marcus, MAE; Van Neer, J; Nijhuis, JG; Roumen, FJME
<x xml:space="preserve">Abstract</x> Objective To assess the effect on mode of delivery of the routine use of labour epidural analgesia (EA) compared with analgesia on request. Design Randomised non‐inferiority trial. Setting One university and one non‐university teaching hospital in The Netherlands. Population Women with a singleton pregnancy in cephalic presentation beyond 36 + 0 weeks' gestation. Methods Participants were randomly allocated to receive either routine EA or analgesia on request. Intention‐to‐treat (ITT) and per‐protocol (PP) analyses were performed, with confidence intervals (CI) calculated for the differences in percentages or means. Main outcome measures Rate of operative delivery (instrumental vaginal or caesarean), labour characteristics, and adverse labour and neonatal outcomes. Results A total of 488 women were randomly allocated to the routine EA (n = 233) or analgesia on request group (n = 255). In the routine EA group, 89.3% (208/233) received EA. According to ITT analysis, 34.8% (81/233) women in the routine EA group had an operative delivery, compared with 26.7% (68/255) in the analgesia on request group (difference 8.1%, 95% CI −0.1 to 16.3). The difference in rate of operative deliveries according to the PP analysis was statistically significant (difference 8.9%, 95% CI 0.4 to 17.4). Inferiority of EA could not be rejected, as in both analyses the upper bound of the confidence interval exceeded the pre‐specified inferiority criterion of +10%. Women in the routine EA group had more adverse effects, including hypotension (difference 9.5%, 95% CI 4.2 to 14.9), and motor blockade (difference 6.8%, 95% CI 1.1 to 12.5). Conclusion Non‐inferiority of routine EA could not be demonstrated in this trial. Routine EA use is likely to lead to more operative deliveries and more maternal adverse effects. The results of our study do not justify routine use of EA.